Compatibility Assessment of Recharge Water with Native Groundwater Using Reactive Hydrogeochemical Modeling in Pinggu, Beijing. Issue 6 (28th October 2013) - Lu, Ying; Du, Xinqiang; Yang, Yuesuo; Fan, Wei; Chi, Baoming; Wang, Zijia; Ye, Xueyan
Abstract A hydrochemical assessment of the local harvested water and groundwater based on field data, lab experiments, and modeling was carried out for a groundwater artificial recharge (GAR) proposal in the Pinggu Basin aquifer. Harvested water chemically regulated by recharge water standard was chosen as an available recharge source in the basin. The sediments at the potential recharge site were characterized to determine the impact of GAR on subsurface hydrochemistry. To model the dynamic hydrochemical changes during GAR, transport process coupled with the geochemical equilibrium was resolved using PHREEQC and a reverse computing process. These were to simulate chemical reactions, soil soluble species dispersion, mineral dissolution and precipitation, and cation exchange in the recharge vadose zone in the Pinggu Basin. The model was validated by a column leaching experiment and applied for field conditions. The prediction results showed NO3−, SO42−, Cl−, and total dissolved solid had peak breakthroughs during the first period of recharge indicating a "washout" phenomenon and then settled down, whilst changes in HCO3−, Ca2+, Mg2+, and pH resulted from carbonate buffering and cation exchange. In the long run, recharge by the harvested water was unlikely to have a negative impact on groundwater quality. Rather caution should be taken for potential chemical clogging induced by dolomite precipitation for a sustainable GAR management.